2001
DOI: 10.1097/00000374-200102000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Third Trimester Binge Ethanol Exposure Results in Fetal Hypercapnea and Acidemia but Not Hypoxemia in Pregnant Sheep

Abstract: A binge ethanol exposure paradigm, three consecutive days per week throughout the third trimester at ethanol doses that created blood ethanol concentrations commonly achieved by human ethanol abusers, resulted in changes in maternal and fetal heart rate, changes in blood pressure, hypercapnea, acidemia, and maternal, but not fetal, hypoxemia. We conclude that in an ovine model system, ethanol doses that create blood ethanol concentrations as high as 260 mg/dl do not result in fetal hypoxemia. Remaining issues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
62
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 32 publications
(74 citation statements)
references
References 28 publications
11
62
1
Order By: Relevance
“…Tissue hypoxia has been proposed as a mechanism involved in prenatal alcoholmediated injury. This hypothesis is supported by the observation that both hypoxia and fetal alcohol exposure induce similar craniofacial defects and neuronal deficits (Bronsky et al, 1986;Cudd et al, 2001). The hippocampal CA1 pyramidal cells and the cerebellar Purkinje cells are both vulnerable to hypoxia (Aitken and Schiff, 1986;Auer et al, 1989;Rees et al, 1999) as well as to alcohol.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Tissue hypoxia has been proposed as a mechanism involved in prenatal alcoholmediated injury. This hypothesis is supported by the observation that both hypoxia and fetal alcohol exposure induce similar craniofacial defects and neuronal deficits (Bronsky et al, 1986;Cudd et al, 2001). The hippocampal CA1 pyramidal cells and the cerebellar Purkinje cells are both vulnerable to hypoxia (Aitken and Schiff, 1986;Auer et al, 1989;Rees et al, 1999) as well as to alcohol.…”
Section: Discussionmentioning
confidence: 88%
“…Therefore, a secondary goal in this study was to assess the changes in maternal blood gases and pH following a binge-like alcohol exposure throughout gestation. We used a weekend binge pattern, a drinking pattern common in women who use alcohol during pregnancy (Caetano et al, 2006;Cudd et al, 2001;Ebrahim et al, 1999;Gladstone et al, 1996;Maier and West, 2001a) and who are more likely to refrain compared with everyday drinkers if convinced that drinking poses a hazard to their baby.…”
mentioning
confidence: 99%
“…Many of the physiologic dependent variables from this exposure paradigm have been reported previously (Cudd et al, 2001).…”
Section: Subjectsmentioning
confidence: 88%
“…However, Smith et al (1989b) found no evidence of hypoxemia in a chronic fetal sheep subjected to acute alcohol exposure. Recently, our report showed that 1.75 g/kg alcohol delivered through the femoral vein of the mother produced maternal, but not fetal, hypoxemia (Cudd et al, 2001). Taken together, it remains unclear at present whether alcohol would produce fetal hypoxia to an extent in utero that will induce neuronal damage or whether neuronal damage can occur in the absence of hypoxic or hypoxemic conditions in the mother or fetus.…”
mentioning
confidence: 87%
See 1 more Smart Citation